Biogas Purification using Modified Red Mud Adsorbent with a Study of the Length of the Adsorbent Column - Wivina Diah Ivontianti; Gayu Ika Putri; Rinjani Ratih Rakasiwi; Syahrul Khairi; Sri Rezeki; Aini Sulastri (Universitas Diponegoro, 2024)
This study used red mud as an adsorbent for biogas purification. However, red mud had to undergo dealumination and calcination processes before being used as an adsorbent. Several acids, including 1 M HCl and 1M H2SO4, were employed in the red mud dealumination process, which was then analysed by XRF and GSA instruments. The results show that the best type of acid for the dealumination process was HCl with a Si/Al ratio, total pore volume, surface area and pore radius of 1.697; 67,081 m2/g; 0.1624 cm3/g; 48.4242 Å. The biogas purification process was carried out using red mud adsorbent dealuminated with HCl by varying the length of the adsorbent column, such as 10, 20 and 30 cm, and the contact time of 5, 10, 15 and 20 min. The optimum column length variation was 30 cm. The results obtained for this variation were a decrease in CO2 content of 292742.30 ppm with an efficiency of 19.08%. The increase in CH4 was 378232.69 ppm with a percentage increase of 240.28%.